PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN ASIMETRI INFORMASI DAN GROUP COHESIVENESS SEBAGAI VARIABEL MODERATING (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Siak) - alrasyid, Salim; Anggraini, Lila; ', Yusralaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to examine the influence of budgeting participate to budgetary slack with asymmetry of information and group cohesiveness as moderating variables. Object of this research is department of the city government in Siak. There are eighty four questionnaires were sent, but only eighty one questionnaires were returned. That data are analyzed by multiple regression method and SPSS program version 19. The results of this research showed that budgetary participate has an effect on budgetary slack with 0,000 significance, the asymmetry of information has interaction between budgetary participate on budgetary slack with 0,009 significance and the group cohesiveness has interaction between budgetary participate on budgetary slack with 0,009 significance. The results of this research also showed that coefficient determinant is 16,4%. The interaction of asymmetry of information gives more strength is 20,7%. Each independent variables, gives the strong influence to dependent variable, it means independents variables could explain dependent variable well. While the remaining influenced by other variables not included in the regression models were not included in this study. All variables also have strong relation with variable dependents in this research.Keywords: Participate, Budgetary, Slack, Asymmetry Of Information And Group Cohesiveness